MODERN UZBEK NATIONAL COSTUMES - M.R. Ergasheva; G.B. Ergasheva (Galaxy International Interdisciplinary Research Journal, 2022)
The composition and history of Uzbek national costumes are the theoretical basis of the ancient costume. This article describes the costumes and customs of the ancient Uzbek national peoples, their formation over the centuries, the changes made to them and their causes and consequences. In the period of global changes in today’s light industry products, "the composition and history of the Uzbek national costume" - it is important to pass on the culture of the past to future generations.